Analisis Manajemen Risiko Keuangan Perusahaan Sektor Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2019 Sampai 2023 - Diana Robiatul Adawiah; Santi Pertiwi Harisandi; Khaerudin Sidik Patoni (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Economic instability in recent years, influenced by the Covid-19 pandemic, the Russia-Ukraine war, and US monetary policy, has triggered high inflation, supply chain disruptions, and a global economic slowdown, including in Indonesia. Indonesia's economic growth slowed from 5.31% in 2022 to 5.05% in 2023, with the manufacturing sector experiencing a significant decline in activity. Many manufacturing companies recorded a drastic decline in revenue, with some even laying off workers to reduce operational costs. Based on Indonesia Stock Exchange data, companies such as PT Sri Rejeki Isman Tbk and PT Asia Pacific Investama Tbk have experienced a drastic decline in revenue continuously in the last five years. This study analyzes the financial risk management of manufacturing companies using the Altman Z-Score to identify the risk of bankruptcy. The results show that some companies are in the bankrupt or gray zone, so a more effective risk management strategy is needed. However, measures such as debt restructuring, raising investor capital, and cost efficiency allowed the companies to continue operating until recently.